Phaseolus vulgaris response to plant growth promoting microorganisms (Scientia Agropecuaria, 2016)
The aim of this study was to analyze the response of P. vulgaris to single inoculation or to PGPM of dose reduced to 50% of NF. In that sense seeds of P. vulgaris were inoculated individually with B. cereus, R. etli or T. harzianum and as a PGPM consortium in a hydroponic system Leonard jars, fed with NH4NO3 (ammonium nitrate) 50%, reduced dose. Under an experimental randomized block design; response variables measured were: percentage and days to germination, plant height and root length, weight fresh/ dry air and root weight (AFW/ADW/RFW/RDW) to seedling and flowering, experimental data were validated by Tukey, p ≤ 0.05. Results showed that P. vulgaris inoculated with R. etli and T. harzianum had 100% and 95.8% germination in 4.8 and 4.5 days respectively and statistically different compared to 91.7% in 7.17 days of P. vulgaris not inoculated at 100% NF had as a Fertilizer Control (FC). At seedling stage of P. vulgaris with T. harzianum and R. etli had 1.12 g and 0.72 g of ADW and of 0.31 and 0.21 g RDW; while P. vulgaris response used as FC with 0.52 g and ADW and 0.19 g of RDW. This supports the positive potential of R. etli and T. harzianum for producing P. vulgaris reduced dose of NF, as well the positive effect of B cereus and microbial consortium in the legume.
Keywords: P. vulgaris; microbial consortium; optimize; nitrogen fertilizer